2020
DOI: 10.1038/s41419-020-2293-7
|View full text |Cite
|
Sign up to set email alerts
|

Antagonizing circRNA_002581–miR-122–CPEB1 axis alleviates NASH through restoring PTEN–AMPK–mTOR pathway regulated autophagy

Abstract: Circular RNAs (circRNAs) have been shown to play critical roles in cancer biology, but their functions in nonalcoholic steatohepatitis (NASH) remain unexplored. Full length of circRNA_002581 was amplified and sequenced, followed by RNA immunoprecipitation, RNA-Fluorescence in Situ Hybridization and dual luciferase reporter gene analysis to confirm the existence of the circRNA_002581-miR-122-CPEB1 regulatory axis in vitro. CircRNA_002581 knockdown was used to study its roles in high concentration of free fatty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 41 publications
1
73
0
Order By: Relevance
“…Most tumors are often accompanied by abnormal activation or inhibition of various molecules and signaling pathways during their development and metastasis ( 22 , 23 ), and AMPK/mTOR signaling is one of the irreplaceable pathways in tumor cells ( 24 ) because it not only regulates the level of intracellular autophagy ( 25 ) but also regulates biological processes such as the proliferation, apoptosis and invasion of tumor cells ( 25 ). AMPK signaling plays a critical role in the development of almost all cancer cells, and its mechanism is to regulate tumor progression through a variety of downstream effector molecules or pathways, such as the mTOR complex ( 26 ). AMPK inhibits the phosphorylation of the mTOR complex and its downstream molecules through various molecular mechanisms, thereby reducing the progression and metastasis of tumor cells ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most tumors are often accompanied by abnormal activation or inhibition of various molecules and signaling pathways during their development and metastasis ( 22 , 23 ), and AMPK/mTOR signaling is one of the irreplaceable pathways in tumor cells ( 24 ) because it not only regulates the level of intracellular autophagy ( 25 ) but also regulates biological processes such as the proliferation, apoptosis and invasion of tumor cells ( 25 ). AMPK signaling plays a critical role in the development of almost all cancer cells, and its mechanism is to regulate tumor progression through a variety of downstream effector molecules or pathways, such as the mTOR complex ( 26 ). AMPK inhibits the phosphorylation of the mTOR complex and its downstream molecules through various molecular mechanisms, thereby reducing the progression and metastasis of tumor cells ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…CircRNA_002581 depletion significantly abolished lipid droplet accumulation and reduced proinflammatory cytokines in mouse NASH models. Further study found that perturbation of circRNA_002581 markedly alleviated the impaired autophagy, manifested by increased LC3‐II/I levels and autophagosome numbers 100 . Moreover, CPEB1‐PTEN‐AMPK‐mTOR signaling has been demonstrated to be associated with autophagy 101 .…”
Section: Circrnas Regulate Lipid Homeostasismentioning
confidence: 95%
“…A recent study implicated increased levels of circRNA_002581 and autophagy induced by FFAs in NASH 100 . CircRNA_002581 upregulation markedly alleviated the repressive effect of miR‐122 on the activity of CPEB1, which may cause pathologic angiogenesis in NASH.…”
Section: Circrnas Regulate Lipid Homeostasismentioning
confidence: 99%
“…In addition to their function as upstream regulators of target mRNAs, microRNAs can themselves serve as downstream targets. For example, circRNA_002581 can suppress miR-122 expression, leading to the upregulation of CPEB1 and phosphorylated-mTOR and the concomitant suppression of autophagy, finally resulting in aggravated steatosis, inflammation, hepatocyte apoptosis, and oxidative stress [28]. In contrast, however, Long et al reported that miR-122 could directly bind to the 3'-UTR of Sirt1, thereby inhibiting its expression and promoting lipogenesis [29].…”
Section: The Role Of Mirnas In Regulating Lipid Metabolism In Nafldmentioning
confidence: 99%